Histopathological Evaluation of Deceased Persons in Lusaka, Zambia With or Without Coronavirus Disease 2019 (COVID-19) Infection: Results Obtained From Minimally Invasive Tissue Sampling. (15th December 2021) - Mudenda, Victor; Mumba, Chibamba; Pieciak, Rachel C; Mwananyanda, Lawrence; Chimoga, Charles; Ngoma, Benard; Mupila, Zacharia; Kwenda, Geoffrey; Forman, Leah; Lapidot, Rotem; MacLeod, William B; Thea, Donald M; et al.
Abstract: Background: Although much has been learned about the pathophysiology of coronavirus disease 2019 (COVID-19) infections, pathology data from patients who have died of COVID-19 in low- and middle-income country settings remain sparse. We integrated minimally invasive tissue sampling (MITS) into an ongoing postmortem surveillance study of COVID-19 in deceased individuals of all ages in Lusaka, Zambia. Methods: We enrolled deceased subjects from the University Teaching Hospital Morgue in Lusaka, Zambia within 48 hours of death. We collected clinical and demographic information, a nasopharyngeal swab, and core tissue biopsies from the lung, liver, and kidneys for pathologic analysis. Individuals were considered eligible for MITS if they had a respiratory syndrome prior to death or a COVID-19+ polymerase chain reaction (PCR) nasopharyngeal swab specimen. Samples were retested using quantitative reverse transcriptase PCR. Results: From June to September 2020 we performed MITS on 29 deceased individuals. PCR results were available for 28/29 (96.5%) cases. Three had a COVID-19+ diagnosis antemortem, and 5 more were identified postmortem using the recommended cycle threshold cut-point <40. When expanding the PCR threshold to 40 ≤ cycle threshold (Ct) ≤ 45, we identified 1 additional case. Most cases were male and occurred in the community The median age at death was 47 years (range 40–64). Human immunodeficiency virus (HIV)/AIDS, tuberculosis, and diabetes were more common among the COVID-19+ cases. Diffuse alveolar damage and interstitial pneumonitis were common among COVID-19+ cases; nonspecific findings of hepatic steatosis and acute kidney injury were also prevalent in the COVID-19+ group. Vascular thrombi were rarely detected. Conclusions: Lung abnormalities typical of viral pneumonias were common among deceased COVID-19+ individuals, as were nonspecific findings in the liver and kidneys. Pulmonary vascular thrombi were rarely detected, which could be a limitation of the MITS technique. Nonetheless, MITS offers a valuable alternative to open autopsy for understanding pathological changes due to COVID-19.